Reduction and Functional Exhaustion of T Cells in Patients With Coronavirus Disease 2019 (COVID-19) - Diao, Bo; Wang, Chenhui; Tan, Yingjun; Chen, Xiewan; Liu, Ying; Ning, Lifen; Chen, Li; Li, Min; Liu, Yueping; Wang, Gang; Yuan, Zilin; Feng, Zeqing; et al. (Frontiers in Immunology, 2020)
BACKGROUND The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has posed great threat to human health. T cells play a critical role in antiviral immunity but their numbers and functional state in COVID-19 patients remain largely unclear. METHODS We retrospectively reviewed the counts of T cells and serum cytokine concentration from data of 522 patients with laboratory-confirmed COVID-19 and 40 healthy controls. In addition, the expression of T cell exhaustion markers were measured in 14 COVID-19 cases. RESULTS The number of total T cells, CD4+ and CD8+ T cells were dramatically reduced in COVID-19 patients, especially in patients requiring Intensive Care Unit (ICU) care. Counts of total T cells, CD8+T cells or CD4+T cells lower than 800/μL, 300/μL, or 400/μL, respectively, are negatively correlated with patient survival. T cell numbers are negatively correlated to serum IL-6, IL-10 and TNF-α concentration, with patients in decline period showing reduced IL-6, IL-10 and TNF-α concentrations and restored T cell counts. T cells from COVID-19 patients have significantly higher levels of the exhausted marker PD-1. Increasing PD-1 and Tim-3 expression on T cells was seen as patients progressed from prodromal to overtly symptomatic stages. CONCLUSIONS T cell counts are reduced significantly in COVID-19 patients, and the surviving T cells appear functionally exhausted. Non-ICU patients, with total T cells counts lower than 800/μL may still require aggressive intervention even in the immediate absence of more severe symptoms due to a high risk for further deterioration in condition.